Biofi lm formation on dental polymeric materials as a basis of microorganism persistence at teeth and periodontium pathology (Эндодонтия Today, 2020)
Study the processes of bacterial colonization and persistence on the surface of polymeric plastics. Plates (1x1 cm) of polymer plastics (polyurethane and acrylic) were used («Dentalur» Russia, «Ftoraks» «Plastic colorless» Stoma, Ukraine). These materials are applied for manufacturing medical dentures. Polymeric plates were incubated in the Luria-Bertani nutrient broth with clinical isolates of P. aeruginosa, S. aureus during 24, 48 hours, 7 and 14 days, 1, 5 and 3 months at a temperature of 37˚C. After incubation, the samples were fi xed in 10% neutral formalin solution. Interaction of bacteria with polymeric materials was studied using scanning electron microscopy (SEM). Traditional SEM dehydration of samples by alcohols or acetone was not carried out, that allowed to study the native structure of extracellular matrix. The stages of interaction between bacteria and surfaces of polymers were investigated. Bacterial biofi lms on the polymeric surfaces provoked their biodestruction changes. The possibility of long-term persistence of human pathogenic microorganisms on artifi cial prostheses is discussing.